1994
DOI: 10.1159/000187805
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Silent Gallstone Disease in Dialysis Patients

Abstract: Gallstone disease was detected in 28% of 119 patients on regular dialysis treatment. The disease was silent in 82% of the patients. Stones were radiolucent in 88% of the cases, radioopaque in 8% and mixed in 4%. Among 49 variables considered, increasing age was the only variable that correlated significantly with increasing prevalence of gallstone disease. Since no relationships were found between gallstones and age or modes of dialysis, it is conceivable that some mechanism(s) linked with the preexisting chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 6 publications
2
27
1
Order By: Relevance
“…Table 1 shows the relevant data of our study in comparison to those of Gladziwa et al [5] and Badalementi et al [6]. Of note, the former included only HD patients.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Table 1 shows the relevant data of our study in comparison to those of Gladziwa et al [5] and Badalementi et al [6]. Of note, the former included only HD patients.…”
Section: Resultsmentioning
confidence: 96%
“…Diabetic nephropathy as the cause of their end-stage renal disease was present in 6.9 and 1.7% of the patients studied by Gladziwa et al [5] and Badalementi et al [6], respectively, whilst they were excluded from our study. The prevalence of CL in comparison to a local healthy population in the study performed by Gladziwa et al [5] was 20.9 versus 29.3% (p = NS) and in the study by Badalementi et al [6] 27.8 versus 8–11% (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Interestingly, the risk of gallstone formation is higher in patients before dialysis but not those undergoing chronic hemodialysis therapy, and in patients with renal transplant than those without transplant. 18,19 However, Badalamenti et al 70 reported the presence of gallstone in 28% of 119 patients on regular dialysis treatment and no relationships were found between gallstones and age or modes of dialysis. Therefore, screening for renal stone and gallstone disease during renal disease may allow early diagnosis and management.…”
Section: Relevance Of Renal and Gallstones In Renal Failurementioning
confidence: 99%
“…Dear Sir, We read with great interest the short com munication by Badalamcnti et al [1], who found a higher prevalence o f gallstone dis ease in patients on regular dialysis treatment (33 of 119; 28%) than in the general Italian population (8-11%). Twenty-nine had gall stones and 4 had had previous cholecystecto mies for colicky gallstones.…”
mentioning
confidence: 99%